Assessing whether rehabilitation programmes from South African mining companies have considered the impacts of climate change - Ndlovu, Zniko Siphokazi (My University, 2016)
The fifth report by the Intergovernmental Panel on Climate Change (IPCC) has a high confidence level that positive radiative forcing due to anthropogenic influences are causing a warming earth surface, and the largest contributor is CO2. Previous research related to mining and climate change, has been inclined to the development of mitigation measures, further addressing how best the mining sector could reduce greenhouse gas emissions which adversely affect the climate system. Minimal research has focused on adaptation measures. The climate - both present and future - is seen as the most vital determinant of rehabilitation success or failure, specifically rainfall patterns and the temperature. Planning for rehabilitation while taking into account climate change, is the first step to enhancing adaptation, allowing successful and resilient rehabilitation. This study aimed to assess whether mining companies operating in South Africa have considered the impacts of climate change on mine rehabilitation. The study achieved this with the use of a qualitative research methodology which included detailed content analysis of documents and transcripts from interviews conducted. From graphical representations of likely future scenarios of climate change, it was identified that all mining companies will be exposed to climate change, thus increasing their vulnerability to future impacts. Secondly, it was identified that only three of the investigated policies and guidelines on closure make a specific mention to climate during the rehabilitation process (MMSD, ITRC and CoM). Through the analysis of Sustainability Reports, it became apparent that climate change issues are prioritised in the selected companies; however, these predominantly transpire as mitigation measures (i.e. energy consumption, GHG emissions and water availability) in response to legal requirements already instituted as well as forthcoming legal frameworks. Only two of the investigated companies have considered climate change during the rehabilitation process of the mine lifecycle. Additionally, the interview process revealed further that climate change is being considered, during the operational phase of the mine lifecycle and the responses are mitigation measures to comply with the legal frameworks. Lastly, from the identified case studies which show how physical climate change impacts can be addressed, an identified trend showed informed decision making by interdisciplinary individuals using credible regional data contributed to some successes. A total of six challenges were identified where after these were seen as strategic components to further catalyse adaptation planning in mine rehabilitation (data sources and management systems, legal framework, collaborations, research and development, funding and sustainability leadership). The findings of this research have created a foundation on which other research, addressing climate change within the South African mining industry, can progress which may further explore the mining company perspective or alternatively the government perspective which was not dealt with thoroughly in this study.
A Research Report submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science. May 2016
Keywords: Climatic changes.; Mineral industries--South Africa.; Mining--South Africa.